The Objectives and Principles of Islamic Education: An Analytical Study on the Orientation of Insan Kamil Formation in the Modern Era - Valentino; Muhammad Saefudin (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the goals and principles of Islamic education in the context of shaping insan kamil (the perfect human being) in the modern era, which is characterized by technological advancement, globalization, and shifting social values. Islamic education is not merely concerned with intellectual development but also emphasizes the harmonious cultivation of spiritual, moral, and social dimensions based on the Qur’an and Hadith. Using a qualitative approach through literature review and conceptual analysis of classical and contemporary sources, this study finds that the primary goal of Islamic education is to form individuals who are faithful, knowledgeable, and virtuous, capable of contributing to modern civilization without losing their Islamic identity. The fundamental principles of Islamic education—namely tawhid (monotheism), balance, responsible freedom, and public benefit—serve as philosophical foundations in responding to the challenges of modernization and secularization. The findings indicate that shaping insan kamil in the modern era requires a reconstruction of the Islamic educational paradigm toward an integrative model that promotes character development, digital literacy, and social ethics grounded in Islamic values. Thus, Islamic education is expected to produce globally competent individuals who remain committed to transcendental principles.